Field Evaluations of Nitrogen-Fixing Products in Grain Sorghum - Kraig L. Roozeboom; Lucas A. Haag; Will Davis; Dorivar A. Ruiz Diaz; Charles W. Rice (Kansas Agricultural Experiment Station Research Reports, 2023)
Nitrogen fertilizer is one of the largest input expenses for grain crops. Biological products are currently available that contain nitrogen-fixing bacteria to supply nitrogen to a crop throughout the growing season. Pivot Bio PROVEN (developed for corn), RETURN (developed for sorghum) and experimental product versions were evaluated in grain sorghum at Manhattan, KS, in 2020, 2021, and 2022. Products were compared with an untreated check at five rates of nitrogen fertilizer. Products were applied at planting in-furrow in a volume of five gallons of water solution per acre. Crop response was characterized by several in-season parameters plus grain parameters and yield. In all years, the interaction of the product with nitrogen fertilizer was not significant for any parameter, indicating that neither version of the product affected how sorghum responded to nitrogen rates. However, most parameters significantly responded to nitrogen fertilizer, indicating that grain sorghum responded to nitrogen supply in all years. In 2020 and 2021, the product did not affect any of the response parameters. In 2022, the experimental product increased canopy normalized vegetative difference index (NDVI) by 8%, biomass by 21%, and nitrogen uptake by 20% early in the growing season compared to the untreated check. Biomass, nitrogen concentration, nitrogen uptake, grain yield, and other parameters quantified at late vegetative stages or later did not differ from the untreated check for either version of the product. Although one product had a positive effect on early-season growth in one year, mid- to late-season biomass and grain yield were not affected.
Keywords: grain sorghum; nitrogen fixation; nitrogen uptake; nitrogen fertilizer; grain yield